Pengaruh Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Wahana Ciptasinatria (WCS Absyena): The Effect of Job Satisfaction and Work Motivation on Employee Performance at PT Wahana Ciptasinatria (WCS Abysena) - Harum Afriana; Frida Aprillia; Sonny Fransisco Siboro (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Employee performance is a crucial factor in determining organizational success. Job satisfaction and work motivation are believed to play significant roles in influencing performance. This study aims to analyze the effect of job satisfaction and work motivation on employee performance, both partially and simultaneously. A quantitative approach was employed using multiple linear regression analysis. Data were collected through questionnaires and analyzed using t-test and F-test. The results indicate that job satisfaction does not have a significant partial effect on employee performance (t = 1.210; sig. = 0.232), while work motivation has a significant partial effect (t = 8.991; sig. = 0.000). Simultaneously, both variables have a significant effect on employee performance (F = 49.258; sig. = 0.000). These findings emphasize the importance of managing work motivation to enhance employee performance within the organization.